Synthesis and electrochemical performance of activated carbon from Lapsi (Choerospondias axillaris) seed biomass for supercapacitor application - Pyakurel, Kaushal; Oli, Dipak; Neupane, Ravi Kiran; Dangi, Sandip; Shrestha, Pitamber; Sharma, Shriram; Joshi, Leela Pradhan (Himalayan Physics, 2025)
The conversion of biomass waste into porous carbon for supercapacitor electrode application represents a promising approach due to the low cost, abundance of raw materials, and environmental advantages. In this study, activated carbon (AC) was synthesized from Lapsi (Choerospondias axillaris) seed biomass by the chemical activation method with zinc chloride (ZnCl2) followed by carbonization in the tubular furnace at 850 oC under continuous nitrogen flow of 100 cc/min for 4 hours. Electrochemical characteristics of the AC electrode were studied in a three-electrode system with a potentiostat device through cyclic voltammetry (CV), galvanostatic charge-discharge (GCD), and electrochemical impedance spectroscopy (EIS). The electrochemical parameters, such as specific capacitance, stability, and impedance were evaluated. The electrode exhibited a specific capacitance of 71.95 F/g at a current density of 1 A/g and maintained 95.71 % capacitance retention over 5000 cycles, demonstrating good electrochemical stability.